Effect of organic substances on the efficiency of Fe(II) to Fe(III) oxidation and removal of iron compounds from groundwater in the sedimentation process = Wpływ substancji organicznych na skuteczność utleniania Fe(II) do Fe(III) oraz usuwania związków żelaza z wody podziemnej w procesie sedymentacji - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the problems with iron removal from groundwater is organic matter. The water samples examined differed in terms of the value of the ratio of the TOC concentration and the concentration of total iron (D). It was concluded that with increase in the coexistence ratio of organic substances and total iron in water, efficiency of Fe(II) to Fe(III) oxidization with dissolved oxygen decreased, while the oxidation time was increasing.
Keywords: groundwater treatment; organic substances; aeration; potassium manganate; Fe(II) oxidation; removal of iron; oczyszczanie wód podziemnych; substancje organiczne; napowietrzanie; manganian potasu; utlenianie Fe(II); usuwanie żelaza